2013
DOI: 10.3233/wor-121529
|View full text |Cite
|
Sign up to set email alerts
|

Does unbalanced gender composition in the workplace influence the association between psychosocial working conditions and sickness absence?

Abstract: INTRODUCTION:Earlier research has shown that bad psychosocial working conditions contribute to sick-leave. Some theorists argue that skewed gender composition can be one of the factors contributing to bad psychosocial working conditions. OBJECTIVES: We examine whether workplace gender composition has an effect on the association between job strain and sick-leave. METHODS AND PARTICIPANTS: Associations were assessed using a case-control study with Swedish data collected in 2008 (n = 5595). RESULTS: Results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
0
18
1
Order By: Relevance
“…Previous research has suggested an influence of gender composition on the association between high strain jobs and sickness absence for both women and men [10]. Our results indicate that when the outcome is self-reported psychological distress rather than sickness absence, gender composition does not influence the association between the psychosocial work environment and the outcome in a corresponding way.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations
“…Previous research has suggested an influence of gender composition on the association between high strain jobs and sickness absence for both women and men [10]. Our results indicate that when the outcome is self-reported psychological distress rather than sickness absence, gender composition does not influence the association between the psychosocial work environment and the outcome in a corresponding way.…”
Section: Discussioncontrasting
confidence: 47%
“…The degree of contact among workers within the same occupation at a workplace can vary, making both occupations and workplace gender composition valid units of analysis. The few studies that have focused on workplaces have analysed gender composition in relation to sickness absence and self-rated health [7-10], whereas mental health remains unexplored. Although mental illness accounts for a substantial part of the sickness absence in Sweden, especially for women [11], there is also a need for studies that focus on the mental ill- health aspects of the gender composition.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research on gender segregation and health has often been based on the hypothesis of tokenism, which suggests that due to a number of group processes, individuals in minority groups are at a higher risk than others of developing ill health. Empirical evidence has, however, not shown increased risks of ill health or sickness absence for the gender in minority, and thus this hypothesis has received very little empirical support [9][10][11][12]. An alternative explanation is that different health-related cultures may develop at workplaces with different gender compositions [13,14].…”
Section: Introductionmentioning
confidence: 99%